Strategi Branding Sentra Wisata Kuliner Jambangan - Putri Tasya Nabillah; Elfina Nur Hidayati; Irmaya Octavia Elrossi Aisyah; Ira Wikartika; Fani Khoirotunnisa; Nurul Azizah (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
In essence, there is a connection between regional autonomy and the tourism sector where the tourism sector is able to accelerate the economic growth of a region. The Surabaya government made efforts to develop and inaugurate a tourist village, namely Kampung Jambangan for the sake of growth, development, and regional development. A branding strategy is needed to provide a good image of the Jambangan Culinary Tourism Center so that visitors or tourists visit this culinary center. The researchers conducted field observations first to determine the type of need to be carried out for branding. Researchers found the right branding steps to increase the number of tourists or visitors to the Jambangan Culinary Tourism Center by doing revitalization, community service, mass gymnastics, and did branding through social media. The purpose of the revitalization activity is to beautify the environment by planting vegetables so that they can reducing the production costs of sellers because they are able to utilize these vegetables. Community service is carried out to improve environmental cleanliness so that a balance between good environmental quality and good food quality is realized. Mass gymnastics is done to attract visitors because there are attractive prizes. Finally, branding through social media is able to expand the reach of audiences so that more and more individuals are familiar with the Jambangan Culinary Tourism Center.